Cricket oviposition trace fossils in palaeosols and their stratigraphic significance: The South American Palaeosol Ichnofossil Ages (SAPIAs) - Genise, Jorge Fernando (2017)
The first insect trace fossil in palaeosols attributed to the oviposition of crickets is represented by openings composed of two to four, but usually three, perforations with a tripartite pattern. This pattern is compatible with the cross section of the distal ovipositor of some crickets. The new ichnotaxon Bellosichnus tripartitus igen. isp. nov. represents a novel architectural design among insect trace fossils in palaeosols. It may reflect true ovipositions or the behavior of testing soil with the ovipositors performed by crickets. In accordance, this trace fossil would be indicative of the surface soil horizon. Bellosichnus tripartitus is abundant in the lower section of the Sarmiento Formation (middle Eocene Casamayoran Age) and it is almost absent before and after this interval in other terrestrial successions of Patagonia. It is a trace fossil with high stratigraphic significance. Bellosichnus tripartitus and other insect trace fossils in palaeosols with similar stratigraphic significance comprise several assemblages, which are representative of different ages along the Cenozoic of southern South America. Such assemblages are typical of particular ages that are named herein South American Palaeosol Ichnofossil Ages (SAPIAs). The SAPIAs run in parallel with the South American Land Mammal Ages (SALMAs). The SAPIAs would be useful to make predictions not only on ages, but also on possible mammal faunas and palaeoenvironments in understudied palaeontological localities.